Sustainable Financing of TVET to Support Skills Development among Vocational and Technical Education Students amidst a dwindling Economy - Nuhu Iliya Nungse; Dornubari Stella Sagbara (International Journal of Home Economics, Hospitality and Allied Research)
In an effort to promote the development of skills among Vocational and Technical students of Colleges of Education (COEs) in Nigeria, this article focused on the evaluation of the most suitable means of financing Technical and Vocational Education and Training (TVET) amidst dwindling economy. The study employed a descriptive survey research design. Mean and standard deviation was used to answer the research questions while Analysis of Covariance (ANOVA) were used to test the hypothesis at .05 level of significance. The researcher solicited for data from six Head of Departments (HOD), 34 Lecturers and five Directors of Academic Planning (DAP) of five COEs to provide answers to the most suitable methods of funding TVET. The instrument for the data collection was a structured questionnaire. The reliability of the instrument was determined using Cronbach alpha method which yielded Cronbach alpha coefficient of .87. The findings revealed that poor funding of the TVET sector in the COEs in North Central Nigeria had compromised the delivery of quality TVET. Hence, Government grants and Provision of special TVET TETFund among others were identified as the suitable means of funding TVET in COEs. It was recommended that adopting a germane source of financing TVET as identified in the current study would go a long way in sustaining TVET toward efficient production of graduates for the world of work. The findings would positively contribute towards resolving a myriad of financing challenges that are ravaging COE training providers to change TVET systems to yield the desired developmental outcomes. Abstract: In an effort to promote the development of skills among Vocational and Technical students of Colleges of Education (COEs) in Nigeria, this article focused on the evaluation of the most suitable means of financing Technical and Vocational Education and Training (TVET) amidst dwindling economy. The study employed a descriptive survey research design. Mean and standard deviation was used to answer the research questions while Analysis of Covariance (ANOVA) were used to test the hypothesis at .05 level of significance. The researcher solicited for data from six Head of Departments (HOD), 34 Lecturers and five Directors of Academic Planning (DAP) of five COEs to provide answers to the most suitable methods of funding TVET. The instrument for the data collection was a structured questionnaire. The reliability of the instrument was determined using Cronbach alpha method which yielded Cronbach alpha coefficient of .87. The findings revealed that poor funding of the TVET sector in the COEs in North Central Nigeria had compromised the delivery of quality TVET. Hence, Government grants and Provision of special TVET TETFund among others were identified as the suitable means of funding TVET in COEs. It was recommended that adopting a germane source of financing TVET as identified in the current study would go a long way in sustaining TVET toward efficient production of graduates for the world of work. The findings would positively contribute towards resolving a myriad of financing challenges that are ravaging COE training providers to change TVET systems to yield the desired developmental outcomes.